Top of the Basilar Syndrome, Clinical Case Presentation and Literature Review (Ictus, 2022)
Cerebral vascular disease includes hemorrhagic and ischemic pathologies, because of the risk factors that prevail in our population, the ischemic spectrum is the most common. Of the ischemic-type, only 20% compromise the posterior circulation, the behavior of this events is usually benign, however, occlusion of the basilar artery has serious neurological repercussions, hence the importance of making an early diagnosis and an early therapeutic intervention that improves the prognosis and recovery of these patients.We present the clinical report of top basilar syndrome, a rare entity, and a review of the literature. There are no studies that report the incidence of this syndrome in Mexico, which is probably the result of underdiagnosis in our country.
Keywords: Basilar Artery; Top of Basilar; Cerebral Ischemic Vascular Disease; Posterior Cerebral Infarction